Negotiating Autonomy: A Narrative Analysis of Women’s Agency and Capital during the Tang Dynasty in Chinese History - Hou, Jing; Tian, Xiaoming; Zhang, Zeyu (Cultural Arts Research and Development, 2026)
This study investigates the agency of women in the Tang Dynasty through Pierre Bourdieu’s theoretical framework of agency and capital, using three female figurines from the Shaanxi History Museum as primary objects of analysis. Depicting women in elaborate makeup, on horseback, and in men’s clothing, these figurines are examined through narrative analysis as storied cultural artifacts that encode gendered identities, performances, and power relations within a patriarchal social structure. Rather than treating the objects as static representations, the study interprets them as embodied narratives that reveal how women’s actions were both enabled and constrained by historical conditions. The findings demonstrate that women’s agency in the Tang Dynasty was not a simple act of resistance against patriarchy but a negotiated and contingent process shaped by the strategic mobilization of economic, cultural, social, and symbolic capital. These women mobilized available capital to assert autonomy within rigid gender norms. The study also acknowledges its limitation in focusing primarily on elite women, as lower-status women are underrepresented in surviving material culture. Narrative inquiry exposes the paradox of historical agency: acts of resistance often depend on structural privilege and remain entangled within the very systems they aim to challenge. This approach underscores the value of narrative methods in uncovering nuanced and context-dependent expressions of female empowerment in the past.